Originally Posted by

**patzer** Again, this is my approach to this problem:

$\displaystyle (\vec{a}\times\vec{b})\cdot\vec{c}=[(3\vec{m}+5\vec{n})\times(\vec{m}-2\vec{n})]\cdot(2\vec{m}+7\vec{n})$$\displaystyle =$

$\displaystyle =[3\vec{m}\times\vec{m}-6\vec{m}\times\vec{n}+5\vec{n}\times\vec{m}-10\vec{n}\times\vec{n}]\cdot(2\vec{m}+7\vec{n})$

$\displaystyle [(\vec{m}\times\vec{m}=0, \vec{n}\times\vec{n}=0, (\vec{m}\times\vec{n})=-(\vec{n}\times\vec{m})]$

so... $\displaystyle (-11\vec{m}\times\vec{n})\cdot(2\vec{m}+7\vec{n})$ I stopped here because I didn't know what to do.

So, here I need your help on this. I appreciate the alexmahone's help, but I'm looking to solve the problem using the facts that were mentioned in problem.